2003
DOI: 10.1063/1.1603726
|View full text |Cite
|
Sign up to set email alerts
|

Transverse nuclear spin relaxation due to director fluctuations in liquid crystals. II. Second-order contributions of the fluctuating director

Abstract: Recently, we have introduced a slow-motional theory for transverse nuclear spin relaxation due to director fluctuations [D. Frezzato, G. Kothe, and G. J. Moro, J. Phys. Chem. B 105, 1281 (2001)]. This method is now generalized to second-order contributions of the fluctuating director. We consider the specific case in which the director is aligned orthogonal to the magnetic field. By exploiting the Gaussian character of director fluctuations, the stochastic Liouville equation for the coupled spin and director d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In this situation, it has been demonstrated that the DF contribution prevails yielding the characteristic dependence (τ) ≅ (τ) ∝ τ 1/2 at large values of τ, while the contribution of the molecular motions dominates at short τ. Unfortunately, low molecular weight nematics are macroscopically aligned by the instrumental magnetic field, and in such a situation an almost τ-independent relaxation rate is predicted. , This is also the present case; in fact, angular measurements in the nematic bulk have been unsuccessful because of the fast reorientation of the molecules with respect to the magnetic field . In the following, we also will show that a reasonable model for molecular reorientational dynamics may yield a basically τ-independent relaxation rate.…”
Section: Analysis Of Dnmr Experimentssupporting
confidence: 57%
See 1 more Smart Citation
“…In this situation, it has been demonstrated that the DF contribution prevails yielding the characteristic dependence (τ) ≅ (τ) ∝ τ 1/2 at large values of τ, while the contribution of the molecular motions dominates at short τ. Unfortunately, low molecular weight nematics are macroscopically aligned by the instrumental magnetic field, and in such a situation an almost τ-independent relaxation rate is predicted. , This is also the present case; in fact, angular measurements in the nematic bulk have been unsuccessful because of the fast reorientation of the molecules with respect to the magnetic field . In the following, we also will show that a reasonable model for molecular reorientational dynamics may yield a basically τ-independent relaxation rate.…”
Section: Analysis Of Dnmr Experimentssupporting
confidence: 57%
“…The theoretical description of nuclear magnetic relaxation driven by DF has been developed. With reference to the case of average director aligned parallel to the magnetic field and to a single deuteron per molecule, a monoexponential dependence of the maximum QE signal vs τ is predicted (i.e., a τ-independent relaxation rate). Because the three deuterons of the central ring of ClPbis11BB-d 3 are basically indistinguishable from the DNMR spectrum within the resolution of the line, one can analyze the data as if a single nucleus would be present.…”
Section: Analysis Of Dnmr Experimentsmentioning
confidence: 99%
“…We choose the ADF frame with the y axis collinear with the Y axis of the LF (see Figure ), therefore the transformation from the LF to the ADF can be specified by the Euler angles Ω = (0, θ B , 0), where θ B is the angle between the static magnetic field B 0 and the average director n̄ at the probe location. The g-tensor component required in eq 2 can be written as ( Z is the unit vector along the static magnetic field) where g ZZ 0 is the component in the absence of director fluctuations ( n ≡ n̄ ), while δ g ZZ is its fluctuating part in the linear approximation with respect to the stochastic variables , Clearly the average vanishes because = 0. It should be stressed that the linear approximation holds in the case of small fluctuation amplitudes, allowing one to neglect in eq 6 higher-order terms (with respect to powers of n x and n y ).…”
Section: The Stochastic Liouville Equationmentioning
confidence: 99%
“…Notice that eq 8 leads to a vanishing δ g ZZ if θ B = 0°, 90°, that is, for the so-called canonical geometries with the average director parallel or perpendicular to the magnetic field. In those situations, second-order terms have to be necessarily accounted for in the expansion of δ g ZZ . However, in the case of vesicles where all orientations θ B contribute, the minor correction to eq 8 due to the appearance of second-order terms can be safely ignored.…”
Section: The Stochastic Liouville Equationmentioning
confidence: 99%
See 1 more Smart Citation